The Flood of 2022 and Its Economic Impacts on the District Kamber-Shahdadkot Kamber, Sindh, Pakistan - Shahzado (`, 2025)
The flood of 2022 was one of the most destructive disasters in the history of Sindh. This research study examines the economic impacts of this flood on the district Kamber-Shahdadkot Kamber. Using a qualitative method, the study analyzes government reports, published literature, and interviews with affected residents. The findings show that the flood caused severe damage to agriculture, irrigation systems, houses, livestock, power supply, and transport networks. Rice crops were almost completely destroyed, thousands of kutcha and pakka houses collapsed, and many people lost their jobs and sources of income. The destruction of roads and bridges increased transportation costs and created shortages of food and daily items, leading to high inflation in the district. Although the Sindh government and NGOs provided some relief in the form of tents, food, cash assistance, and dewatering pumps, most residents remained dissatisfied with the government’s response. Overall, the study concludes that the economic impact of the 2022 flood on Kamber-Shahdadkot Kamber was extremely high and long-lasting, worsening poverty, unemployment, and food insecurity in the district. Keywords: Flood of 2022, Economic Impacts, Kamber-Shahdadkot Kamber, Sindh